DNA-PK inhibitor reduces cell viability on colorectal cancer - Bui, Khac Cuong; Tran, Phuong Linh; Nguyen, Thi Mai Ly (Tạp chí Y Dược Huế, 2024)
Background: The MinIONTM is a portable DNA sequencing device that can sequence 16S rRNA genes. 16S rRNA genes are found in all bacteria and can be used to identify bacterial species. By sequencing 16S rRNA genes and analyzing the sequences for antibiotic resistance genes, we can identify bacteria that are resistant to antibiotics. Materials and methods: Ten clinical specimens, including two sputum samples and eight urine samples from outpatients and inpatients, were subjected to pathogenic bacteria identification and antibiotic resistance detection using the MinIONTM portable device. Results: The MinIONTM sequencer successfully identified species levels in ten clinical samples. Based on investigating the 16S rRNA sequencing with AMRA on EPI2ME of Nanopore Technologies, we found eight mutations. Conclusions: The MinION sequencer is a valuable tool in medical laboratories for swiftly identifying bacterial species and determining their antibiotic resistance profiles, contributing to efficient antimicrobial resistance diagnostics